Effects Of Rehabilitation On Biochemical Indicators And Markers Of The Antioxidant System In Alcoholic Subjects Attending De-Addiction Centre - SAMEER R KULKARNI,; K. PRATIBHA RAVINDRA,; C. Y. DHUME,; EDMOND RODRIGUES,; SUNANDA AMONKAR, (International Journal of Pharma and Bio Sciences, 2012)
Chronic alcohol consumption induces an increase in oxidative stress. There are studies which indicate changes in the activity of antioxidant enzymes and the concentration of lipid peroxidation products in the blood due to alcohol consumption. The aim was to study the effect of 21-days rehabilitation programme on endogenous antioxidant enzymes like erythrocyte Superoxide Dismutase(S.O.D.), Glutathione Peroxidase (GPx.) and blood Glutathione(G.S.H.) in male alcohol–dependent patients (n=160).Erythrocyte activities of SOD, GPx and blood GSH levels were measured, initially and after rehabilitation. The activities of SOD and GPx in erythrocytes and blood GSH levels of alcohol-dependent persons were statistically significantly lower than in the control group both before and after detoxification. However, after detoxification, there was an increase in the activity of SOD, GPx and blood GSH levels compared to that before detoxification. Our results indicate that alcohol rehabilitation improves the biochemical indicators of alcohol abuse and activities of endogenous antioxidants.